Effects of physical activity participation on cognitive impairment in older adults population with disabilities - Lim, Seung-Taek; Kwak, Hyo-Bum; Kang, Ju-Hee; Chang, Eunwook; Joa, Kyung-Lim; Park, Hee-Jung; Park, Dong-Ho (Frontiers in Public Health, 2024)
Background Existing research on the association between cognitive function and physical activity in the older adults population with disabilities is limited. Additionally, there is a need to explore avenues for enhancing the longevity and quality of life among these individuals. Objective This study aimed to investigate the independent and joint associations between cognitive function and levels of physical activity in the older adults population with disabilities. Methods A total of 315 older adults adults (men = 182, women = 133), identified with disabilities based on medical evaluation, were recruited from the first survey of the Korean Longitudinal Study of Aging (KLoSA). Participants underwent assessments for cognitive function, physical activity (PA), activities of daily living (ADLs), instrumental activities of daily living (IADLs), and grip strength. Results ADLs (p < 0.001) and IADLs (p < 0.001) scores were significantly higher in the male normal cognitive group compared to both the male and female cognitive impairment groups. In an unadjusted model, disabled older adults individuals who did not meet the recommended PA guidelines showed an increased odds ratio for cognitive dysfunction (OR = 2.29, 95% CI = 1.32–3.97). Those participating in PA at least 1 day per week also demonstrated an elevated odds ratio (OR = 1.22, 95% CI = 1.08–1.38) for cognitive dysfunction compared to those who engaged in regular PA. A negative correlation was observed between K-MMSE scores and grip strength (r = 0.448, p < 0.001). Conclusion This study provides robust evidence that disabled older adults individuals who do not meet the recommended guidelines for PA or who do not participate in PA at least once a week have an increased likelihood of cognitive impairment compared to those who are regularly active.